Event Pop Up Market Event as a Marketing Strategy for Online Purchasing Decisions in Elevenia.co.id (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
This study aims to find out an overview of online purchasing decisions of visitors to the Pop-Up Market event and to find out the Pop-Up Market event as Elevenia's marketing strategy. To find out this overview of online buying decisions, researchers use a qualitative approach, which aims to explore the extent of online purchasing decisions of visitors to the Pop-Up Market event. The data used for this study are primary data and secondary data. The results of the research analysis using in-depth interviews of actors involved in Pop Market events (organizers, sellers and visitors) in the Seller Zone Elevenia. The success of the Pop-Up Market event is due to the increasing number of customers who visit this event as well as make transactions. In terms of marketing strategy, this Pop-Up Market event was also successful. Elevenia needs an effective and efficient marketing strategy with the limitations they have, it turns out that this event provides new things while helping Elevenia in terms of visitors and transactions.